1982
DOI: 10.1007/bf00987802
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a female-produced sex pheromone of the western corn rootworm

Abstract: A sex pheromone has been isolated and identified from virgin females of the western corn rootworm (WCR),Diabrotica virgifera virgifera LeConte. The synthesized compound, racemic 8-methyl-2-decanol propanoate, was equal in attraction to the natural pheromone when tested in the field as a trap bait against three taxa ofDiabrotica known to respond to pheromone extracts from female WCR. Five taxa (D. virgifera virgifera; D. virgifera zeae Krysan and Smith, Mexican corn rootworm;D. longicornis barberi Smith and Law… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
3

Year Published

1986
1986
2008
2008

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(26 citation statements)
references
References 12 publications
0
22
0
3
Order By: Relevance
“…The case of the Osaka and Japanese beetles is the first one where its importance in a reciprocal behavioral agonist-antagonist context is clearly demonstrated. Nevertheless, there is evidence in the literature to suggest that this phenomenon may occur in other species of Coleoptera (17)(18)(19) and Lepidoptera (20). The pheromone of the Western corn rootworm, Diabrotica virgifera, has been identified as 8-methyl-2-decyl propanoate (17).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The case of the Osaka and Japanese beetles is the first one where its importance in a reciprocal behavioral agonist-antagonist context is clearly demonstrated. Nevertheless, there is evidence in the literature to suggest that this phenomenon may occur in other species of Coleoptera (17)(18)(19) and Lepidoptera (20). The pheromone of the Western corn rootworm, Diabrotica virgifera, has been identified as 8-methyl-2-decyl propanoate (17).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, there is evidence in the literature to suggest that this phenomenon may occur in other species of Coleoptera (17)(18)(19) and Lepidoptera (20). The pheromone of the Western corn rootworm, Diabrotica virgifera, has been identified as 8-methyl-2-decyl propanoate (17). When the four possible stereoisomers were tested in the field, it was observed that Diabrotica barberi was attracted to the (2R, 8R)-isomer and inhibited by the (2S, 8R) (18), while Diabrotica longicornis was attracted by the (2S, 8R)-and inhibited by the (2R, 8R)-stereoisomer (19).…”
Section: Resultsmentioning
confidence: 99%
“…The femaleproduced sex pheromone system seems to be wide spread in Diabrotica genus. In general, virgin females exhibit a potent attraction to males (Guss et al 1982). Sex pheromones also have been isolated and identified from virgin females.…”
Section: Resultsmentioning
confidence: 99%
“…Sex pheromones also have been isolated and identified from virgin females. In the virgifera group, the compound racemic 8-methyl- (Guss et al 1982). Another chemical identified was the 6,12-dimethylpentadecan-2-one, from D. balteata LeConte virgin females (Chuman et al 1987).…”
Section: Resultsmentioning
confidence: 99%
“…34 This compound is also attractive to several Diabrotica species. 35,36 Males of D. virgifera virgifera and D. virgifera zeae responded to (2R,8R)-and (2S,8R)-7, while D. porracea responded exclusively to (2S, 8R)-7.…”
Section: 7-dimethylnonyl Propanoate (7)mentioning
confidence: 99%